Interventional Pulmonology and Pulmonary Hypertension - Updates on Specific Topics [Working Title] 2019
DOI: 10.5772/intechopen.86812
|View full text |Cite
|
Sign up to set email alerts
|

2-Methoxyestradiol in Pulmonary Arterial Hypertension: A New Disease Modifier

Abstract: Pulmonary arterial hypertension (PAH), a debilitating and incurable disease, predominantly develops in women. Estradiol metabolism leads to the production of numerous metabolites with different levels of estrogenic activity and very often opposing biological effects. Dysregulated estradiol metabolism was recently linked to the penetrance, progression, and prognosis of the disease. Ongoing clinical trials are examining the effects of estradiol synthesis/signaling inhibition in patients with PAH. In this chapter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 164 publications
(172 reference statements)
0
8
0
Order By: Relevance
“…As in the previous hypoxia model, female sex is protective in the rat model of MCT-PH and ovariectomy aggravates PH while exogenous administration of estrogens, in both males and females, improves RV function (Tofovic et al, 2006;Umar et al, 2011). Estradiol metabolites such as 2 ME or 2hydroxyestradiol are able to prevent and retard the progression of MCT-induced PH in rats by attenuating pulmonary vascular remodeling and RV hypertrophy, and reducing proliferative and inflammatory responses in the lungs (Tofovic et al, 2005;Tofovic et al, 2010). The use of an ERα agonist rescued MCT-PH and protected RV myocardium by restoring RV apelin and bone morphogenetic protein receptor type 2 (BMPR2) (Frump et al, 2021).…”
Section: Evidence From Experimental Animal Models Of Pulmonary Arterial Hypertensionmentioning
confidence: 88%
See 1 more Smart Citation
“…As in the previous hypoxia model, female sex is protective in the rat model of MCT-PH and ovariectomy aggravates PH while exogenous administration of estrogens, in both males and females, improves RV function (Tofovic et al, 2006;Umar et al, 2011). Estradiol metabolites such as 2 ME or 2hydroxyestradiol are able to prevent and retard the progression of MCT-induced PH in rats by attenuating pulmonary vascular remodeling and RV hypertrophy, and reducing proliferative and inflammatory responses in the lungs (Tofovic et al, 2005;Tofovic et al, 2010). The use of an ERα agonist rescued MCT-PH and protected RV myocardium by restoring RV apelin and bone morphogenetic protein receptor type 2 (BMPR2) (Frump et al, 2021).…”
Section: Evidence From Experimental Animal Models Of Pulmonary Arterial Hypertensionmentioning
confidence: 88%
“…A detailed description of sex hormone metabolism and signaling, published elsewhere (Austin et al, 2013;Lahm et al, 2014;Lahm and Kawut, 2017;Tofovic and Jackson, 2019;Tofovic and Jackson, 2020), is beyond the scope of this review. Briefly, the three main estrogenic steroids are 17-β estradiol (estradiol or E2), the primary active sex hormone in the female, estrone (E1) and estriol (E3).…”
Section: Overview Of Sex Hormones Synthesis and Metabolismmentioning
confidence: 99%
“…The angiogenic properties of E2 are in striking contrast to the strong antiangiogenic effects of its major non-estrogenic metabolite 2ME. The other biological effects of 2ME relevant to PAH (Figure 2) have been reviewed previously [166].…”
Section: Opposing Effects Of E2 and 2me On Angiogenesis (Key Role Of mentioning
confidence: 99%
“…2ME, via a multitude of actions (Figures 2 and 3), can not only provide pulmonary vascular and RV protection, but also oppose the potential detrimental effects of E2 due to redirection of its own metabolism and metabolism of AA in PAH. Thereby, 2ME could be considered as both mediator and corrector of E2 s action and a new disease modifier in PAH [166].…”
Section: Concluding Remarks and Future Directionsmentioning
confidence: 99%
“…Finally, 2ME not only mediates (at least in part) the beneficial effects of estradiol in PH, but also 2ME exhibits opposing effects to estradiol on several processes relevant to the underlying pathophysiology of PH, including angiogenesis, metabolic reprograming, inflammation, and immunity [12]. Therefore, recently we suggested that 2ME should be viewed as a disease modifier in women with PH [20]. The objective of this study was to examine the preventive and curative effects of 2ME in chronic hypoxia (CH)-induced PH in male rats.…”
Section: Introductionmentioning
confidence: 97%